ANALISIS URAIAN TUGAS TENAGA ADMINISTRASI SEKOLAH BIDANG KESISWAAN DI SEKOLAH MENENGAH PERTAMA KABUPATEN SIJUNJUNG - Amanda Amanda; Rusdinal Rusdinal; Hadiyanto Hadiyanto; Yulianto Santoso (Jurnal Administrasi Pendidikan Indonesia, 2026)
The implementation of the job descriptions of school administrative staff in the field of student affairs plays an important role in supporting the effectiveness of administrative services. However, its implementation in Junior High Schools in Sijunjung Regency has not been widely studied empirically. This study aims to describe the implementation of the job descriptions of school administrative staff in the field of student affairs in Junior High Schools in Sijunjung Regency based on the aspects of clarity of duties, responsibilities, and authority. The study used a quantitative approach with descriptive methods. The study population was 76 school administrative staff, with a sample of 43 respondents selected through cluster random sampling technique. Data were collected using a Likert scale questionnaire and analyzed descriptively using the Respondent Achievement Level (TCR). The results showed that the implementation of the job descriptions of school administrative staff in the field of student affairs was in the sufficient category with an average score of 3.75 and a TCR of 75.08%. The responsibility indicator achieved the highest achievement (76.54%), followed by clarity of duties (74.84%) and authority (73.55%), all of which were in the sufficient category. This finding shows that the implementation of job descriptions has been running, but still requires strengthening, especially in the aspect of clarity of division of tasks, responsibilities, and authority to comply with the provisions of the Minister of National Education Regulation Number 24 of 2008. The results of the study provide empirical information that can be used as a basis for evaluation in increasing the effectiveness of student administration management in schools.